The transcription factor CREM drives an inflammatory phenotype of T cells in oligoarticular juvenile idiopathic arthritis - Kim Ohl; Helge Nickel; Halima Moncrieffe; Patricia Klemm; Anja Scheufen; Dirk Föll; Viktor Wixler; Angela Schippers; Norbert Wagner; Lucy R. Wedderburn; Klaus Tenbrock (BMC, 2018)
Abstract Background Inflammatory effector T cells trigger inflammation despite increased numbers of Treg cells in the synovial joint of patients suffering from juvenile idiopathic arthritis (JIA). The cAMP response element (CREM)α is known to play a major role in regulation of T cells in SLE, colitis, and EAE. However, its role in regulation of effector T cells within the inflammatory joint is unknown. Methods CREM expression was analyzed in synovial fluid cells from oligoarticular JIA patients by flow cytometry. Peripheral blood mononuclear cells were incubated with synovial fluid and analyzed in the presence and absence of CREM using siRNA experiments for T cell phenotypes. To validate the role of CREM in vivo, ovalbumin-induced T cell dependent arthritis experiments were performed. Results CREM is highly expressed in synovial fluid T cells and its expression can be induced by treating healthy control PBMCs with synovial fluid. Specifically, CREM is more abundant in CD161+ subsets, than CD161− subsets, of T cells and contributes to cytokine expression by these cells. Finally, development of ovalbumin-induced experimental arthritis is ameliorated in mice with adoptively transferred CREM−/− T cells. Conclusion In conclusion, our study reveals that beyond its role in SLE T cells CREM also drives an inflammatory phenotype of T cells in JIA.